Advances in polymer electrolyte design strategies for highly efficient supercapacitors and Zn-based batteries - Puthiyaveetil, Priyanka Pandinhare; Babu, Athira; Kurian, Maria; Kurungot, Sreekumar (Chemical Communications, 2025)
Electrolytes play a crucial role in the performance of electrochemical energy storage systems, such as batteries and supercapacitors. Their main function is to act as a medium for ion transport between the electrodes, which is essential for the charge and discharge processes. Beyond this, the electrochemical performance of the device is strongly affected by the various properties of the electrolytes such as their ionic conductivity, chemical, thermal and electrochemical stability, chemical compatibility, etc. The intrinsic limitations of the aqueous electrolytes such as their decomposition during high voltage operations has led to the development of better electrolytes for batteries and supercapacitors. These included non-aqueous electrolytes, inorganic solid-state electrolytes, and gel polymer electrolytes. This feature article reviews the various approaches to designing a highly efficient polymer electrolyte for the targeted application along with the suitable device fabrication strategy adopted in the current literature to achieve a balanced electrochemical performance compared with a liquid electrolyte-based device.

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.